Analisis faktor-faktor yang mempengaruhi perilaku minat wajib pajak orang pribadi dalam menggunakan e-Filing (Studi di Kabupaten Ende) - Antonius Gunawan Ghani; Dewi Kusumowati (University of Merdeka Malang, 2020)
This study aims to examine whether perceptions of usefulness, perceptions of ease, perceptions of volunteerism, perceptions of social factors influence the behavior of the personal interests of taxpayers in the use of e-Filing in Ende Regency. Data obtained from the results of filling out the questionnaire by respondents totaling 86 individuals taxpayers who use e-Filing in Ende Regency. Questionnaire data were tested with validity, reliability, classic assumption tests, and to analyze hypotheses using multiple linear regression analysis, F test, and T test using the SPSS version 16.0 application. The results showed that the perception of usefulness and perception of social factors significantly influence the interest in e-Filing behavior. While perceptions of ease and volunteerism perceptions do not significantly influence the interest of taxpayers' behavior in using e-Filing. Keywords: perceived usefulness, perceived ease, volunteerism perception, perception of social factors,interest in the use of e-Filing.